HYPERTRIGLYCERID-ASSOCIATED ACUTE PANCREATITIS: CLINICAL CHARACTERISTICS AND TREATMENT RESULTS - Onishchenko, Mariia; Shchigel, Ivanna; Ivanets, Tetiana; Levchenko, Liudmyla; Gorlach, Andrey (The Ukrainian Scientific Medical Youth Journal, 2020)
The aim of the study is to evaluate the clinical characteristics of patients with hypertriglyceride associated acute pancreatitis. A single-center observational study of a series of cases was performed on the basis of the Kyiv Department of Surgery for Liver, Pancreas and Bile Tracts named after V.S. Zemskov in the period from 2018 to 2019. Investigation includes patients with acute pancreatitis and hypertriglyceridemia (the triglycerides level is more than 1.7 mmol/l). Exclusion criteria: patients with acute pancreatitis with normal triglyceride levels, patients with acute pancreatitis with elevated triglycerides, that have not been treated enough. All patients were evaluated by Charlson index of comorbidity, body mass index, alcohol history, relapses and severity of disease. All patients were monitored throughout inpatient treatment, from hospitalization to discharge to home or death. The end point of the study was the discharge of the patient to home after the elimination of the manifestations and complications of acute pancreatitis or death of the patient. The 234 patients who were hospitalized and treated with a diagnosis of acute pancreatitis, 27 patients had hypertriglyceridemia and 3 of them were excluded from the study. The study involved 24 patients. Therefore, the frequency of acute pancreatitis associated with high triglycerides was 11.5% (27/234), with the average level of triglyceridemia was 10.1 ± 2.4 mmol / l (range 5.8 - 13.6 mmol / l) , 75% of patients (18/24) had moderate hypertriglyceridemia (2.3 - 11.2 mmol / l), 25% (6/24) - severe (11.2 - 22.4 mmol / l) . The median age was 32 years (quarterly interval 31.5 - 35 years). There were 18 men (75%) and 6 women (25%). Alcohol-induced pancreatitis was observed in 17 (70.8%) patients with hypertrtiglyceridemia. The median body mass index is 28.9 kg / m 2. Normal weight was 33% (8/24) patients, excessive - 25% (6/24), obesity I stage - 29% (7/24) obesity II stage - 8% (2/24) obesity III stage - 4% (1/24). The Charlson comorbidity index ranged from 0 to 5 points, in 1 patient it was 5 points, in 3 patients - 2 points, in 3 patients - 1 point. Diabetes mellitus were in 25% of patients (6 /24), two of them was diagnosed at first. Recurrent cases of disease were in 58.3% of patients (14 /24), 10 of 14 had a history of two cases of acute pancreatitis. In 71% (17 /24) observed a light stage of the disease, 25% (6 /24) - pancreatitis medium degree of severity and in 4% (1 /24) of the patient severe pancreatitis. Mortality was 4%. Conclusions. The frequency of hypertriglyceride-associated acute pancreatitis is 11.5%. In light, moderate and severe pancreatitis, the average degree of hypertriglyceridemia (blood triglycerides 2.3 -11.2mmol/l) was prevailed. Hypertriglyceride-associated acute pancreatitis has no specific complications, but has a tendency to recurrence. Patients with hypertriglyceridemia need constant laboratory monitoring (determination of triglycerides), pharmacological therapy and follow-up to prevent the development of acute pancreatitis